Identification of gas reservoirs and determination of their parameters by combination of radioactive logging methods - Kulyk, V.V.; Bondarenko, M.S. (Геофизический журнал, 2016)
The paper proposes a new approach for using a combination of radioactivity logging (neutron and density logging), which allows determining a set of gas reservoir parameters (nature of saturation, true porosity, gas saturation) taking into account influence of the pressure and temperature conditions of occurrence. Analysis of the ways of averaging the neutron-apparent porosity and the density-apparent porosity for obtaining the true porosity was made. Method of determination of gas saturation, which uses the same combination of radioactivity logging as in determining the true porosity of gas reservoirs, was developed. The results presented in the paper, were obtained over a wide interval of depth (up to 10 km). Application of developed approaches for determination of petrophysical parameters of gas reservoirs is demonstrated by the example of cased coalbed methane well. Запропоновано новий підхід до використання комплексу радіоактивного каротажу - нейтрон-нейтронного (ННК) і гамма-гамма каротажу (ГГК), який дозволяє визначати сукупність параметрів газових колекторів (характер насичення, істинна пористість, коефіцієнт газонасиченості) з урахуванням впливу термобаричних умов залягання. Виконано аналіз варіантів усереднення позірних пористостей за ННК і за ГГК при отриманні істинної пористості. Розроблено спосіб визначення коефіцієнта газонасиченості, який використовує той же комплекс, що й при визначенні істинної пористості газових колекторів. Приведені результати отримано для широкого інтервалу глибин (до 10 км). Застосування розвинутих підходів до визначення петрофізичних параметрів газових колекторів продемонстровано на прикладі обсадженої метановугільної свердловини.